Developing a clinically relevant classification to predict mortality in severe leptospirosis - Rajapakse, S.; Rodrigo, C.; Haniffa, R. (My University, 2010)
BACKGROUND: Severe leptospirosis requires critical care and has a high mortality. We reviewed the literature to identify factors predicting mortality, and such predictors were classified according to the predisposition, infection, response, organ dysfunction (PIRO) concept, which is a risk stratification model used in severe sepsis. MATERIAL AND METHODS: PUBMED was searched for all articles (English), with the key word leptospirosis in any field, within the last 20 years. Data were collected from 45 relevant papers and grouped into each component of the PIRO model. RESULTS: THE FOLLOWING CORRELATED WITH INCREASED MORTALITY: predisposition - increasing age and chronic alcoholism; infection - leptospiraemic burden; response - hemodynamic disturbances, leukocytosis; organ dysfunction - multiple organ dysfunction syndrome, pulmonary involvement and acute renal failure. CONCLUSIONS: Further research is needed to identify the role of infecting serovars, clinical signs, inflammatory markers, cytokines and evidence of hepatic dysfunction as prognostic indicators. It is hoped that this paper will be an initiative to create a staging system for severity of leptospirosis based on the PIRO model with an added component for treatment-related predictors.